Efecto inmunomodulador y antitumoral del extracto de brassica oleracea l. var. botrytis “coliflor” sobre células inmunes en mus musculus var. swiss isogénicos con cáncer experimental - González Siccha, Anabel Doris (2015)
Objective: To determine immunomodulatory and antitumor effect of the extract of Brassica oleracea L. var. Botrytis "Cauliflower" on immune cells in Mus musculus var. Swiss isogenic with experimental cancer. Biological material: Cauliflower collected Simbal-Trujillo, 35-45 g mice. Method: Induction cancer Benzopyrene, Control Group (CG no treatment), treated: GPa (Quercetin), GP1 (ESPC: D=10mg/Kg/pc); GP2 (ESPC: D=20mg/Kg/pc). It was determined: antibody titer, total count (CTL), differential leukocyte (CDL), body weight for 0, 30, 60 and 90 days; number, size, and evaluation of tumors. Results: The extract has secondary metabolites: steroids, saponins, tannins and flavonoids glycosylated quercitin-3-diglucoside-7-diglucoside and kaempferol-3-diglucoside-7-glucoside. GPa, GP1 and GP2 elevated antibody titer compared to GC (P<0.05). Presents difference CTL, percentage neutrophils, lymphocytes and monocytes compared with GC (P<0.05); among GPa, GP1 and GP2 no significance (P>0.05). So, it could be argued that ESPC has same effect quercetin pattern on antibody titer, CTL and CDL. GC presented greater number and size of tumors, decreased body weight, presented alopecia, asthenia and conjunctival xerosis due to energy and metabolic imbalance (P <0.01). Tumor cell evaluation shows apoptosis in GPa, GP1 and GP2. Therefore, we conclude that the ESP cauliflower contains kaempferol and quercetin appear to act synergistically; to quercetin is attributed immunomodulatory effect for their anti-inflammatory and antioxidant properties so increases antibody titer and lymphocytes; and antitumor effect for their pro-apoptotic properties so reduces the proliferation of neoplastic cells.